THE GOVERNMENTAL STRUCTURE OF THE USA: LEGISLATIVE, EXECUTIVE AND JUDICIAL ACTIVITIES, THE US CONGRESS AIN (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This comprehensive article provides an in-depth analysis of the  governmental structure of the United States of America, focusing on the three key  branches: Legislative, Executive, and Judicial. It delves into the distinct roles and  functions of each branch, emphasizing the critical role of the US Congress within the  Legislative Branch. The article offers a clear breakdown of the Senate and the House of  Representatives, detailing their responsibilities and powers